Synthesis of Ag/ZnO/Bentonite Nanocomposite Using Hagenia Abyssinica Plant Leaf Extract for Antibacterial Studies - Adisu Girma (ASTU, 2022)
In 2017, the World Health Organization (WHO) estimated that by 2050, multibacterial infections, which are caused by two or more bacterial species, will cause more deaths than cancer due to the antimicrobial resistance. This implies the need to identify and assess new antibacterial agents. The aim of this study was to synthesize environmentally friendly Ag/ZnO/Bentonite NCs for antibacterial studies by a green method. The Ag/ZnO/Bentonite NC was synthesized successfully using H. abyssinica plant leaf extract as reducing and capping agents. Ag NPs, ZnO NPs, Ag/Bentonite NCs, ZnO/Bentonite NCs were also synthesized to compare their antibacterial activity with that of Ag/ZnO/Bentonite NCs. The synthesized materials were characterized by UV-Vis-DRS, XRD, FTIR, HR-TEM, and SEM. UV-Vis-DRS results confirmed the formation of NPs and NCs with the optical band gap (Eg) of Ag NPs, ZnO NPs, Ag/Bentonite NCs, ZnO/Bentonite NCs, and Ag/ZnO/Bentonite NCs 2.5, 3.07, 2.9, 3.2, and 3.3 eV respectively. The XRD pattern of Ag and ZnO showed peaks of Ag and ZnO NPs, confirming the formation of the silver (fcc) and hexagonal phase (wurtzite structure) ZnO. The XRD patterns of the binary and ternary nanocomposites also confirmed the formation of Ag/Bentonite, ZnO/Bentonite and Ag/ZnO/Bentonite NCs. The average crystalline sizes (D) of Ag NPs and ZnO NPs were estimated at about 7.4 nm and 9.4 nm respectively, from the XRD pattern of Ag/ZnO/Bentonite NCs. FTIR spectra confirmed the presence of hydroxyl, carbonyl, alkyl, amide, and other functional groups on the surface of NPs and NCs. TEM analysis revealed the formation of Ag and ZnO NPs, with an average particle size of 10.8 nm and 18.5 nm respectively, which agreed with XRD results analysis. The antibacterial activities of the composites were evaluated against Gram-negative E. coli ATCC 25922 and Gram-positive S. aureus ATCC 25923 by the disk diffusion and broth dilution methods. Better antibacterial activity with maximum values of 14.3  0.3 and 17 mm at 10 mg/mL dosage toward E. coli and S. aureus respectively for the ternary (Ag/ZnO/Bentonite) NCs was observed. The MIC and MBC observed for Ag/ZnO/Bentonite NCs were 156.25 µgmL-1 , and 312.5 µgmL-1 for E. coli and 78.125 µgmL-1 , 156.25 for S. aureus, respectively. The results revealed that the Ag/ZnO/Bentonite composite is a promising bactericide that can be used as an antibacterial agent
Keywords: Antibacterial activity, Bentonite, Disk diffusion, Green synthesis, Nanoparticles, Nanocomposite.